Sumbangsih Bukti-bukti Arkeologi Alkitab dalam Membangun Iman Percaya Masa Kini - Siringoringo, Lumayan Maya; Suhadi, Suhadi (Jurnal Teologi Berita Hidup, 2024)
This study examines the role of archaeological evidence in strengthening the Christian faith today. Amid rampant doubt and skepticism, archaeological discoveries offer historical verification and contextualization of biblical stories. This research reviews important archaeological discoveries related to people, places, and events in the Bible. This evidence demonstrates the historical accuracy of the Bible and strengthens confidence in the stories it contains. Furthermore, this study discusses how archaeological findings allow Christians to better understand and appreciate the meaning of sacred texts. Although archaeology cannot prove all aspects of the Christian faith, it offers valuable tools for strengthening faith and combating doubt. By connecting the Bible with physical evidence, archaeology helps build bridges between past and present, allowing Christians to connect with the heritage of their faith more deeply.Â Penelitian ini mengkaji peran bukti arkeologi dalam memperkuat iman Kristen di masa kini. Di tengah maraknya keraguan dan skeptisisme, penemuan arkeologi menawarkan verifikasi sejarah dan kontekstualisasi kisah-kisah Alkitab. Penelitian ini meninjau penemuan arkeologi penting yang terkait dengan orang, tempat, dan peristiwa dalam Alkitab. Bukti-bukti ini menunjukkan keakuratan historis Alkitab dan memperkuat kepercayaan terhadap kisah-kisah yang terkandung di dalamnya. Lebih lanjut, penelitian ini membahas bagaimana temuan arkeologi memungkinkan umat Kristiani untuk lebih memahami dan menghargai makna teks suci. Meskipun arkeologi tidak dapat membuktikan semua aspek iman Kristen, ia menawarkan alat berharga untuk memperkuat iman dan memerangi keraguan. Dengan menghubungkan Alkitab dengan bukti fisik, arkeologi membantu membangun jembatan antara masa lalu dan masa kini, memungkinkan umat Kristiani untuk secara lebih mendalam terhubung dengan warisan iman mereka.